Hubungan Pengetahuan Dan Sikap Dengan Perilaku Pencegahan Covid-19 Pada Tenaga Kesehatan Di FKTP Nusa Tenggara Timur - Amalia, Annisa; Lada, Christina Olly; Sidarta, Sagita; Wungouw, Herman (Universitas Nusa Cendana, 2023)
Background : World Health Organization (WHO) announced COVID-19 as a pandemic in 2020. COVID-19 is a disease that is highly contagious but can be prevented by means of appropriate management. Knowledge and attitudes and behavior about how to treat COVID-19 are things that need to be considered by health workers, this can have a major impact in protecting health workers from exposure, and reducing the death rate of health workers so that it helps in dealing with the COVID-19 pandemic. Purpose : To determine the relationship between knowledge and attitudes with COVID-19 prevention behavior among health workers in the FKTP of East Nusa Tenggara Province. Methods : This study was an observational analytic study with a cross sectional design for health workers in East Nusa Tenggara. The determination of the sample size is measured using a correlative analytic formula and the results are 243 respondents. A total of 243 respondents met the inclusion criteria and were willing to be asked to fill out a knowledge questionnaire totaling 16 questions, attitudes as many as 15 questions and behavior as many as 14 questions about the prevention of COVID-19. Data from respondents will be excluded if they do not complete the questionnaire completely and fill out the questionnaire with the same identity. This research was analyzed by univariate then bivariate using the Kendall Tau test. Result : From 243 respondents, it was found that all respondents had high knowledge. In attitudes, 98.8% have a good attitude and 1.2% have a bad attitude. In behavior, there are 97.1% have good behavior and 2.9% have poor behavior. The results of the bivariate test using the Kendall Tau test for the relationship between Knowledge and Behavior obtained p = 0.001 (p <0.05) and for the relationship between Attitude and Behavior, the result was p = 0.002 (p <0.05). Conclusion : There is a significant relationship of knowledge and attitude with covid-19 prevention behaviors in health worker at first rate healthcare east nusa tenggara.